Effect of native and modified starches on nutritional and physiological performance of wild juveniles of red grouper (Epinephelus morio) - Castillo, Ana; Callejas, Leticia; Álvarez-González, Carlos Alfonso; Maldonado, Carlos; Cuzon, Gerard; Gaxiola-Cortés, Martha Gabriela (Ecosistemas y Recursos Agropecuarios, 2018)
The aim of this study was to evaluate carbohydratesutilization by wild red grouper Epinephelus morio.Juveniles were fed during 93 d on a selection of starches: native raw cornstarch (RCS), waxy cornstarch (WCS), raw potato starch (RPS) and gelatinized potato starch (GP) at 20% inclusion level. The best growth was obtained in fish fed cornstarch either native raw of waxy cornstarch (p<0.05). Hepatosomatic index and blood glucose (40 mg dL-1) were similar as well as hematocrit values (50%) (p>0.05), whereas glycogen content increased up to 200 mg g-1with waxy cornstarch. Specific activity of a-glucosidase and α-amylase remained stable (p>0.05). Hepatic glycolytic enzymes increased with raw native and waxy cornstarch (p<0.05); metabolic enzyme glucose 6 phosphate dehydrogenase (G6P-DH) was activated with raw native cornstarch (p<0.05) while pyruvate kinase (PK) remained stable regardless of treatments (p>0.05). Hexokinase (HK1) and glucokinase (GK) varied according to carbohydrate source: values were higher with cornstarches than potato starches (p<0.05). Pentose monophosphate shunt (HMS) remained not altered by starch sources (p>0.05). In final, the low size of granules from cornstarch favored the assimilation in liver of wild juveniles red grouper.